Metalloproteomic analysis of liver proteins isolated from broilers fed with different sources and levels of copper and manganese - Aparecida Martins, Renata [UNESP]; de Almeida Assunção, Andrey Sávio [UNESP]; Cavalcante Souza Vieira, José [UNESP]; Campos Rocha, Leone [UNESP]; Michelin Groff Urayama, Priscila [UNESP]; Afonso Rabelo Buzalaf, Marília; Roberto Sartori, José [UNESP]; de Magalhães Padilha, Pedro [UNESP] (Springer Nature, 2024)
Supplementing minerals beyond dietary requirements can increase the risk of toxicity and mineral excretion, making the selection of more bioavailable sources crucial. Thus, this work aimed to use metalloproteomics tools to investigate possible alterations in the hepatic proteome of broilers fed with diets containing two sources (sulfate and hydroxychloride) and two levels of copper (15 and 150 ppm) and manganese (80 and 120 ppm), totaling four treatments: low Cu/Mn SO4, high Cu/Mn SO4, low Cu/Mn (OH)Cl and high Cu/Mn (OH)Cl. The difference in abundance of protein spots and copper and manganese concentrations in liver and protein pellets were analyzed by analysis of variance with significance level of 5%. The Cu and Mn concentrations determined in liver and protein pellets suggested greater bioavailability of hydroxychloride sources. We identified 19 Cu-associated proteins spots, 10 Mn-associated protein spots, and 5 Cu and/or Mn-associated protein spots simultaneously. The analysis also indicated the induction of heat shock proteins and detoxification proteins in broilers fed with high levels of copper and manganese, suggesting the involvement of these proteins in metal tolerance and stress.